MAXIMIZING MANAGEMENT AND UTILIZATION OF VILLAGE CASH LAND AND LAND OF PELUNGGUH WARD GUWOSARI PAJANGAN - Riyanto; Adji Suradji Muhammad (Yayasan Wayan Marwan Pulungan, 2023)
This research is entitled